Investigation of efficacy and acquired resistance for EGFR-TKI plus bevacizumab as first-line treatment in patients with EGFR sensitive mutant non-small cell lung cancer in a Real world population. (March 2020) - Zeng, Liang; Xiao, Lili; Jiang, Wenjuan; Yang, Haiyan; Hu, Dandan; Xia, Chen; Li, Yizhi; Zhou, Chunhua; Xiong, Yi; Liu, Li; Liao, Dehua; Guan, Rui; et al.
Highlights: The first study to evaluate acquired resistance for 1 st line EGFR-TKI plus Bevacizumab (A + T). Mutation ratio of T790 M was decreased in A + T group compared with single T group. SMAD4 mutations and EGFR p.V834 L were regarded as novel acquired resistance to A + T. Real world data proves A + T significantly extends PFS with acceptable safety profile. Abstract: Objectives: We aimed to investigate the clinical efficacy of EGFR tyrosine kinase inhibitor (TKI, T) plus bevacizumab (an antiangiogenic therapy, A) in a real-world population and to provide insights into their mechanism of resistance. Methods: This study included 256 NSCLC patients harboring EGFR sensitizing mutations ( EGFR 19del and L858R) who underwent nextgeneration sequencing (NGS) with 168-gene panel prior to treatment between Jan 2015 to Aug 2018. Cohort A included 60 patients treated with A + T; while cohort B consisted of 120 patients treated with EGFR-TKI monotherapy with the patients identified using Propensity Score Matching (Ratio of 1:2). Clinical outcomes and potential resistance mechanism were evaluated. Results: Baseline clinical characteristics were not significantly different between Cohort A and B. Compared with cohort B, cohort A had significantly better overall response rate (95% vs 74.2%, p = 0.001) and longer median progression-free survival (PFS, 16.5m vs.12.0 m, HR = 0.7, p = 0.001). Until Jan 2019, 31 and 103 patients in cohort A and B, respectively, were evaluated with progressive disease and underwent tissue re-biopsy and NGS profiling with 168-gene panel. In cohort B, T790M was the predominant acquired resistance mechanism, detected in 51.5% (53/103) of progressive tumors, followed by amplifications in EGFR (15.5%, 16/103) and MET (6.8%, 7/103). Contrastingly, cohort A had a significantly lower rate of T790 M mutation (35.5%, 11/31, p = 0.0003), followed by mutations in TP53 (29.0%, 9/31), RB1 (9.7%, 3/31), SMAD4 (3.2%, 1/31) and EGFR V834 L (3.2%, 1/31) and amplifications in EGFR (9.7%, 3/31), and MET (6.5%, 2/31). Conclusion: Treatment with first-line A + T significantly extends the time to progression and increases the response rate with acceptable safety profile. T790 M was the most common acquired resistance mechanism but it was less common in patients who received A + T.